Wear-resistant material for sealing high-speed rotating part and preparation method of wear-resistant material
By adding components such as hydroxylated modified polyether ether ketone, composite fiber and lithium magnesium silicate sol to wear-resistant materials, the problems of surface cracking and poor wear resistance under high impact pressure are solved. , achieving better wear resistance and longer service life.
Patent Information
- Application Number
- CN202510033309.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2045-01-09
AI Technical Summary
When existing wear-resistant materials are used in sewage or chemical waste liquid with high impact pressure, cracks are prone to surface, and wear resistance becomes worse, resulting in a shortening of the service life of high-speed rotating parts.
采用碳化硅、羟基化改性聚醚醚酮、复合纤维和硅酸镁锂溶胶等组分的耐磨材料,通过复杂的组分配比和制备工艺,提高材料的耐磨性和力学性能。
The wear-resistant material is not prone to cracking on the surface under high impact pressure, has excellent wear resistance and can significantly extend the service life of high-speed rotating parts.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wear-resistant materials, and in particular to a wear-resistant material for sealing a high-speed rotating part and a preparation method thereof. Background Art
[0002] In mechanical equipment, when the rotating parts of a rotating machine come into contact with the stationary parts, radial friction or axial collision and wear between the moving and static parts will occur. In severe cases, the entire machine may be damaged. Therefore, wear-resistant materials need to be installed between the rotating parts and the stationary parts to meet the anti-wear requirements.
[0003] In the prior art, one of the commonly used wear-resistant materials on high-speed rotating parts is ceramic materials, which include aluminum oxide, silicon nitride, silicon carbide, etc., and have the advantages of high hardness, high strength, wear resistance, high temperature resistance, etc., so they are widely used in high-speed rotating parts. A Chinese patent with an authorization publication number of CN102504204B discloses a wear-resistant material composited with organic polymer and silicon carbide and a preparation method thereof, including two components A and B. Component A mainly includes 100 parts of epoxy resin, 2-3 parts of silane coupling agent, and 550-560 parts of silicon carbide; component B includes 25 parts of carboxyl-terminated liquid rubber, 15-20 parts of amine curing agent, 2-4 parts of accelerator, and 140-150 parts of silicon carbide. The two components A:B are mixed in a weight ratio of 4:1.
[0004] However, in the prior art, epoxy resin and silicon carbide are used to make wear-resistant materials. Epoxy resin has excellent adhesion, which helps to better process and shape with silicon carbide. However, epoxy resin is brittle. When the wear-resistant material is applied to media such as sewage with high impact pressure, the surface of the above-mentioned wear-resistant material is prone to cracking and the wear resistance deteriorates, which is not conducive to maintaining a long service life of high-speed rotating parts. Summary of the invention
[0005] Based on the above technical problems, the present application provides a wear-resistant material for sealing high-speed rotating parts and a preparation method thereof. When used in media such as sewage and chemical waste liquid with high impact pressure, it has excellent wear resistance and can maintain a long service life.
[0006] In the first aspect, the present application provides a technical solution using the following: A wear-resistant material for sealing high-speed rotating parts, which is applied to the friction working area between rotating parts and stationary parts. The wear-resistant material comprises the following components in parts by weight: 40-60 parts of silicon carbide, 10-30 parts of hydroxylated modified polyetheretherketone, 3-10 parts of composite fiber, 5-15 parts of magnesium silicate lithium sol, and 1-2 parts of silane coupling agent.
[0007] By adopting the above technical scheme, hydroxylated modified polyetheretherketone and magnesium silicate lithium sol are added to the wear-resistant material system of silicon carbide. As an upgraded material of epoxy resin, polyetheretherketone has excellent wear resistance, chemical corrosion resistance, peeling resistance and mechanical strength; magnesium silicate lithium has thickening, thixotropy and film-forming properties, and strong adsorption capacity. Its sol helps to increase the adhesion of polyetheretherketone and can also form a film on the surface of rotating parts, while maintaining a low expansion rate and water absorption rate; at the same time, hydroxylation modification of polyetheretherketone helps to provide more active sites for the coupling introduction of magnesium silicate lithium molecules, thereby ensuring the full reaction of hydroxylated modified polyetheretherketone and magnesium silicate lithium sol, so that the prepared wear-resistant material can be used in media such as sewage and chemical waste liquid with high impact pressure, and the surface is not prone to cracking and has excellent wear resistance, thereby maintaining a long service life of high-speed rotating parts.
[0008] Furthermore, the wear-resistant material comprises the following components in parts by weight: 45-55 parts of silicon carbide, 15-25 parts of hydroxylated modified polyetheretherketone, 5-8 parts of composite fiber, 8-12 parts of magnesium silicate lithium sol, and 1.2-1.8 parts of silane coupling agent.
[0009] By adopting the above technical solution, the addition amount of each component in the wear-resistant material is optimized, so that the mechanical properties and wear resistance of the wear-resistant material can be made better.
[0010] Furthermore, the particle size of the silicon carbide is 30-50 μm.
[0011] By adopting the above technical scheme, it is helpful to evenly disperse silicon carbide in the reaction system, thereby realizing the preparation of wear-resistant materials with excellent wear resistance and mechanical properties. However, if the particle size of silicon carbide is too large, it is not easy to be evenly dispersed in the reaction system, and the density between silicon carbide particles is reduced, which will affect the wear resistance and mechanical properties of the wear-resistant material; if the particle size of silicon carbide is too small, agglomeration will occur, and the wear-resistant material cannot be guaranteed to have excellent wear resistance.
[0012] Furthermore, the hydroxylation degree of the hydroxylated modified polyetheretherketone is 70%-85%.
[0013] By adopting the above technical scheme, the surface roughness of the hydroxylated modified polyetheretherketone is significantly increased, which helps to provide more active sites, thereby improving the reaction activity with the lithium magnesium silicate sol. In this scheme, the hydroxylation degree of the hydroxylated modified polyetheretherketone is 70%-85%, which helps to provide more active sites for the coupling introduction of the lithium magnesium silicate molecules, thereby improving the binding activity with the lithium magnesium silicate sol. When the prepared wear-resistant material is used in media such as sewage and chemical waste liquid with high impact pressure, its surface is not prone to cracking and has excellent wear resistance.
[0014] Furthermore, the magnesium silicate lithium sol is prepared according to the following method: Mix polyvinyl alcohol and deionized water, and raise the temperature to 90-95°C while stirring until the polyvinyl alcohol is dissolved to form a polyvinyl alcohol aqueous solution with a mass concentration of 15%-20%; Then, lithium magnesium silicate is added into deionized water and magnetically stirred for 30-45 minutes to obtain a lithium magnesium silicate aqueous dispersion having a mass concentration of 0.8%-1.2%; Adding diethylene glycol butyl acetate to the lithium magnesium silicate aqueous dispersion, wherein the added mass of diethylene glycol butyl acetate is 1-5% of the lithium magnesium silicate dispersion, stirring evenly, then slowly dripping the polyvinyl alcohol aqueous solution, stirring at a temperature of 50-60° C. for 30-40 minutes, to obtain a mixed solution; The mixed solution is degassed in a vacuum degasser to obtain a magnesium silicate lithium sol.
[0015] By adopting the above technical scheme, the viscosity of the dispersion must be strictly controlled in the preparation of lithium magnesium silicate sol. When lithium magnesium silicate is dissolved in deionized water and the lithium magnesium silicate dissolved in deionized water is mixed with a polyvinyl alcohol aqueous solution, the gelation of lithium magnesium silicate is easily produced due to the action of hydrogen bonds. In the present application, diethylene glycol butyl ether acetate is added, and the interaction between it and the lithium magnesium silicate molecules is greater than the interaction between polyvinyl alcohol and lithium magnesium silicate, which helps to reduce the physical cross-linking points of lithium magnesium silicate between polyvinyl alcohol molecular chains. Therefore, the addition of diethylene glycol butyl ether acetate can reduce the gelation of lithium magnesium silicate sol, thereby realizing the stable preparation of lithium magnesium silicate sol; at the same time, diethylene glycol butyl ether acetate has excellent film-forming properties, which helps to further improve the wear resistance of wear-resistant materials.
[0016] Furthermore, the composite fiber is a mixture of carbon fiber and aramid fiber in a mass ratio of 1.8-2:1.
[0017] By adopting the above technical scheme, carbon fiber can effectively reinforce polyetheretherketone, but the surface of carbon fiber is very easy to wear. Aramid fiber is compounded with carbon fiber. Since the molecular chain of aramid fiber is rigid and very dense, it can effectively prevent substances from passing through the fiber gaps, thereby compensating for the defect of easy wear of carbon fiber. The prepared composite fiber has excellent mechanical reinforcement, wear resistance, chemical corrosion resistance and good stress fatigue resistance.
[0018] Furthermore, the carbon fiber is a short-cut carbon fiber with a length of 1-3 mm, and the aramid fiber is a short-cut aramid fiber with a length of 100-200 μm.
[0019] By adopting the above technical solution, carbon fibers within the above length ratio range are compounded with aramid fibers, and the aramid fibers can fill the gaps in the carbon fibers. The two can produce a synergistic effect, which helps to improve the mechanical properties and wear resistance of the wear-resistant material.
[0020] In a second aspect, the present application provides a method for preparing a wear-resistant material for sealing a high-speed rotating part, using the following technical solution: A method for preparing a wear-resistant material for sealing a high-speed rotating part, comprising the following steps: The composite fiber is placed in the magnesium silicate lithium sol and immersed at room temperature for 1-1.5 hours to obtain the magnesium silicate lithium sol immersed in the fiber; The hydroxylated modified polyetheretherketone is heated and melted, and the magnesium silicate lithium sol impregnated with the fiber and the silane coupling agent are added under stirring, and the mixture is mixed for 10-30 minutes; Add silicon carbide, mix and stir for 30-45 minutes, extrude and granulate to obtain wear-resistant material.
[0021] By adopting the above technical scheme, the composite fiber is not easy to be directly dispersed in polyetheretherketone, so the composite fiber is pre-impregnated in the lithium magnesium silicate sol, and then the sol is added to the melt of hydroxylated modified polyetheretherketone and evenly blended, which helps to improve the stability of the preparation process. At the same time, the prepared wear-resistant material is evenly dispersed and has good wear resistance and mechanical properties.
[0022] Furthermore, before the composite fiber is placed in the magnesium silicate lithium sol, hydroxy silicone oil is evenly dripped onto the surface of the composite fiber, and the composite fiber is sealed and stored for 12-24 hours.
[0023] By adopting the above technical solution, hydroxy silicone oil permeates the surface of the composite fiber, which is beneficial to modify the surface of the composite fiber with hydroxyl groups. There are a large number of hydroxyl groups in the magnesium silicate lithium sol, which is beneficial to uniformly disperse the composite fiber in the magnesium silicate lithium sol.
[0024] In a third aspect, the present application provides an application of a wear-resistant material for sealing a high-speed rotating part, using the following technical solution: The invention discloses an application of a wear-resistant material for sealing a high-speed rotating part. The wear-resistant material can be used for processing a sealing part between a high-speed rotating part and a stationary part.
[0025] In a possible implementation, the sealing member may be a sealing ring, a bearing ring, a bearing seat, etc.
[0026] In summary, the present application has at least one of the following beneficial effects: (1) In the present application, hydroxylated modified polyetheretherketone, magnesium silicate lithium sol and composite fiber are added to the wear-resistant material system of silicon carbide, so that the prepared wear-resistant material can be used in media such as sewage with high impact pressure, and the surface is not prone to cracking, has excellent wear resistance, and maintains a long service life of high-speed rotating parts; (2) The present application adopts hydroxylated modified polyetheretherketone, the surface roughness of which is significantly increased, which helps to provide more active sites, thereby improving the binding activity with magnesium silicate lithium sol, so that when the prepared wear-resistant material is used in media such as sewage and chemical waste liquid with high impact pressure, its surface is not prone to cracking and has excellent wear resistance.
[0027] (3) The viscosity of the dispersion liquid must be strictly controlled in the preparation of lithium magnesium silicate sol in the present application. When lithium magnesium silicate is dissolved in deionized water or when lithium magnesium silicate dissolved in deionized water is mixed with a polyvinyl alcohol aqueous solution, the lithium magnesium silicate is easily gelled due to hydrogen bonding. In the present application, diethylene glycol butyl acetate is added, and the interaction between it and the lithium magnesium silicate molecules is greater than the interaction between polyvinyl alcohol and lithium magnesium silicate, which helps to reduce the physical cross-linking points of lithium magnesium silicate between polyvinyl alcohol molecular chains. Therefore, the addition of diethylene glycol butyl acetate can reduce the gelation of lithium magnesium silicate sol, thereby achieving stable preparation of lithium magnesium silicate sol; at the same time, diethylene glycol butyl acetate has excellent film-forming properties, which helps to further improve the wear resistance of wear-resistant materials. DETAILED DESCRIPTION
[0028] In order to make the invention purpose, technical solution and beneficial technical effect of the present application clearer, the present application will be described in detail below. It should be noted that the various aspects, features, implementation methods and advantages described in the present application may be compatible and / or may be combined together.
[0029] Unless otherwise specified, the meanings of the technical terms in this specification are the same as those generally understood by those skilled in the art.
[0030] The polyetheretherketone of the present application was purchased from Changchun Jida Special Plastic Engineering Research Co., Ltd., with an average particle size of 7 μm. Lithium magnesium silicate was purchased from Nanjing Hemmings New Material Technology Co., Ltd., with an average particle size of 500 nm.
[0031] Preparation Example of Hydroxylated Polyetheretherketone Preparation Example 1-3: Weigh about 150 g of polyetheretherketone into a glass dish, place the glass dish in a vacuum drying oven, set the drying temperature to 80 °C, and dry for 12 h; Take a certain amount of dried polyetheretherketone, place it in a high-speed grinder for crushing, and then screen the crushed polyetheretherketone with a 30-mesh sieve (aperture 0.6 mm); 100 mL of dimethyl sulfoxide was measured and placed in a 500 mL three-necked flask, 4 g of the crushed polyetheretherketone was weighed and poured into the three-necked flask, and then 0.8 g of sodium borohydride was weighed and transferred into the three-necked flask; Place the three-necked flask in an oil bath (dimethyl silicone oil), immerse 1 / 2 of the three-necked flask in the oil bath, set the oil bath temperature to 120°C, stir at a speed of 85 r / min, and react for 6-10 hours; When the reaction is completed, the temperature of the three-necked flask is lowered to room temperature, filtered with microporous filter paper, and washed with anhydrous ethanol, deionized water, and hydrochloric acid solution in sequence; After the filtration is completed, the filtrate is discarded, the filter cake is placed in a glass dish, and then the glass dish is placed in a vacuum drying oven, the drying temperature is set to 80°C, and dried for 12 hours; Grinding: Move the dried polyetheretherketone into a mortar and grind it briefly. Store the ground hydroxylated polyetheretherketone in a plastic bag for later use.
[0032] The difference between Preparation Examples 1-3 is that the reaction time in step (4) is different.
[0033] sample Reaction time (h) Degree of hydroxylation (%) Preparation Example 1 6 70 Preparation Example 2 8 80 Preparation Example 3 10 85 Preparation Example of Lithium Magnesium Silicate Sol Preparation Example 4-7 The following is a detailed description taking Preparation Example 4 as an example.
[0034] Preparation Example 4: Mix 10 g of polyvinyl alcohol with 50 g of deionized water, and heat to 90° C. while stirring until the polyvinyl alcohol is completely dissolved, to prepare a polyvinyl alcohol aqueous solution; Then, 1 g of lithium magnesium silicate was added into 100 g of deionized water and magnetically stirred for 30-45 min to obtain a lithium magnesium silicate aqueous dispersion; Adding diethylene glycol butyl acetate to the lithium magnesium silicate aqueous dispersion, wherein the added mass of diethylene glycol butyl acetate is 3% of the lithium magnesium silicate dispersion, stirring evenly, then slowly dropping a polyvinyl alcohol aqueous solution, stirring at 60° C. for 30 minutes, to obtain a mixed solution; The mixed solution is degassed in a vacuum degasser to obtain a magnesium silicate lithium sol.
[0035] The difference between Preparation Examples 4-7 is that the added mass of diethylene glycol butyl ether acetate is different.
[0036] Table 1 Addition mass of diethylene glycol butyl ether acetate in Preparation Example 4-7 sample Diethylene glycol butyl ether acetate (%) Viscosity of Lithium Magnesium Silicate Sol (cP) Preparation Example 4 3 1299 Preparation Example 5 1 1858 Preparation Example 6 5 1578 Preparation Example 7 0 3666 Example
[0037] Examples 1-5 A wear-resistant material for sealing a high-speed rotating part, the wear-resistant material comprising the following components: silicon carbide, hydroxylated modified polyetheretherketone, composite fiber, magnesium silicate lithium sol, silane coupling agent; wherein the particle size of silicon carbide is 30 μm, the hydroxylated modified polyetheretherketone adopts Preparation Example 1, the magnesium silicate lithium sol adopts Preparation Example 4, and the silane coupling agent adopts KH-550; The preparation method of the wear-resistant material is: The short-cut carbon fibers with a length of 1-3 mm and the short-cut aramid fibers with a length of 100-200 μm are mixed in a mass ratio of 2:1 to prepare composite fibers; Evenly drip hydroxy silicone oil onto the surface of the composite fiber, wrap the composite fiber dripped with hydroxy silicone oil with a plastic film, and seal and store for 12 hours; Then the composite fiber was placed in magnesium silicate lithium sol and immersed at room temperature for 1 hour; The lithium magnesium silicate sol impregnated with the composite fiber was stirred at a speed of 35 r / min; Add the hydroxylated modified polyetheretherketone into a single screw extruder, heat it to 370-420°C, add the magnesium silicate lithium sol impregnated with the fiber and the silane coupling agent under stirring, and blend for 30 minutes; Add silicon carbide, mix and stir for 45 minutes, and extrude to form.
[0038] The difference between Examples 1-5 is that the formulations of the wear-resistant materials are different.
[0039] Table 2 Formulations of wear-resistant materials of Examples 1-5 sample Silicon carbide (g) Hydroxyl modified polyetheretherketone (g) Composite fiber (g) Lithium magnesium silicate sol (g) Silane coupling agent (g) Example 1 40 10 3 5 1 Example 2 45 15 5 7 1.2 Example 3 50 20 7 10 1.5 Example 4 55 25 8 12 1.8 Example 5 60 30 10 15 2 Embodiment 6-7 The difference between Example 6-7 and Example 2 is that the hydroxylated polyetheretherketone adopts Preparation Example 2-3.
[0040] Table 3 The hydroxylated polyetheretherketone in Examples 6-7 is different sample Hydroxylated polyetheretherketone Example 6 Preparation Example 2 Example 7 Preparation Example 3
[0041] Example 8 The difference between this embodiment and embodiment 2 is that the particle size of silicon carbide is different. In this embodiment, the particle size of silicon carbide is 50-80 μm.
[0042] Examples 9-11 The difference between Examples 9-11 and Example 2 is that different lithium magnesium silicate sols are used.
[0043] Table 4 The magnesium silicate lithium sols of Examples 9-11 are different sample Lithium magnesium silicate sol Example 9 Preparation Example 5 Example 10 Preparation Example 6 Embodiment 11 Preparation Example 7
[0044] Comparative Example A wear-resistant material comprises the following components by mass: 40g of silicon carbide, 10g of polyetheretherketone, 3g of carbon fiber, and 1g of silane coupling agent; wherein the particle size of the silicon carbide is 30μm, the carbon fiber is short-cut carbon fiber with a length of 1-3mm; and the silane coupling agent is KH550.
[0045] The wear-resistant material is prepared by the following method: Evenly drip hydroxy silicone oil onto the surface of the composite fiber, wrap the composite fiber dripped with hydroxy silicone oil with a plastic film, and seal and store for 12 hours; Add polyetheretherketone into a single screw extruder, heat to 370-420°C, add the composite fiber and silane coupling agent under stirring, and blend for 30 minutes; Add silicon carbide, mix and stir for 30-45 minutes, and extrude to form.
[0046] Detection methods: Tensile strength: Mechanical testing was performed using a CTM-C104 electronic universal control testing machine. The sample was placed in a 170×24×6cm strip mold, weighing 25g, heated and melted, with a pre-compression pressure of 7.5MPa for 3min; the strip mold was then placed in a flat vulcanizer for compression molding, with a compression pressure of 7.5MPa and a holding time of 10min. The tensile properties were tested using a CTM-C104 microelectronic control universal testing machine in accordance with GB / T1040.2-2006, with a loading speed of 5mm / min, and 5 samples were tested in each group. The tensile strength was the average of the experimental values.
[0047] Impact strength: According to GB / T1043.1-2008, the simply supported beam notch impact toughness of the sample is tested in an impact testing machine (at room temperature). The impact strength of the material is δ, in KJ / m 2 .
[0048] δ = F / A (a) In formula (a), F is the fracture impact energy, in J; A is the fracture cross-sectional area, in mm 2 .
[0049] Abrasion resistance: Friction and Wear Test The wear performance of the sample was tested on an MMS-2A friction and wear tester. The sample was a 50mm*40mm*3mm sample made of the wear-resistant materials of the embodiments and comparative examples, and the counterpart was an AISI52100 steel ring. The ambient temperature was 23-25°C, the relative humidity was 40%, and under water lubrication conditions, the sample was subjected to a friction and wear test on the grinding block at a sliding speed of 200r / min and a steel ring under a load of 200N. The friction time was 40min, and the friction and wear coefficient and specific wear rate were calculated.
[0050] The test results of Examples 1-11 and Comparative Examples are shown in Tables 5-6 Table 5 Test results of mechanical properties of Examples 1-11 and Comparative Examples sample Tensile strength (MPa) <![CDATA[Impact strength (KJ / m 2 )]]> Surface condition Example 1 88.2 7.13 The surface is smooth, complete and free of fine lines Example 2 98.6 8.96 The surface is smooth, complete and free of fine lines Example 3 99.1 9.22 The surface is smooth, complete and free of fine lines Example 4 98.7 9.15 The surface is smooth, complete and free of fine lines Example 5 88.6 7.82 The surface is smooth, complete and free of fine lines Example 6 101.3 9.83 The surface is smooth, complete and free of fine lines Example 7 99.66 9.22 The surface is smooth, complete and free of fine lines Example 8 96.5 8.32 The surface is smooth, complete and free of fine lines Example 9 93.6 8.22 The surface is smooth, complete and free of fine lines Example 10 94.8 8.39 The surface is smooth, complete and free of fine lines Embodiment 11 85.6 6.68 The surface is slightly rough with fine lines Comparative Example 55.3 3.86 Rough surface, cracks Table 6 Test results of friction and wear properties of Examples 1-11 and Comparative Examples sample Friction coefficient <![CDATA[Specific wear rate (×10 -6 mm 3 / N·m)]]> Example 1 0.28 0.79 Example 2 0.23 0.68 Example 3 0.20 0.59 Example 4 0.21 0.63 Example 5 0.30 0.81 Example 6 0.20 0.70 Example 7 0.26 0.72 Example 8 0.32 0.79 Example 9 0.26 0.71 Example 10 0.28 0.72 Embodiment 11 0.34 0.86 Comparative Example 0.38 0.94 Combined with the test results of Examples 1-5, Comparative Examples and Tables 5-6, it can be seen that the addition of hydroxylated modified PEEK, magnesium silicate lithium sol and composite fibers to the silicon carbide material in the present application can significantly improve the mechanical properties and wear resistance of the wear-resistant material, and the surface is smooth, complete and free of fine lines, wherein the mass proportion of silicon carbide is 55%-62%, the proportion of hydroxylated polyetheretherketone is 20%-25%, the proportion of composite fibers is 6.8%-8%, and the proportion of magnesium silicate lithium sol is 10%-12%.
[0051] Combined with the test results of Example 2, Examples 6-7 and Table 5, it can be seen that the degree of hydroxylation of polyetheretherketone will also affect the mechanical properties and wear resistance of the wear-resistant material. This is because the surface roughness of polyetheretherketone is significantly increased by hydroxylation, which helps to provide more active sites, thereby improving the reaction activity with magnesium silicate lithium sol, promoting the full reaction of magnesium silicate lithium sol with hydroxylated modified polyetheretherketone, and making the prepared wear-resistant material have excellent mechanical properties and wear resistance.
[0052] Combining the test results of Example 2 and Example 8 and Table 5, it can be seen that when the particle size of silicon carbide is 50-80 μm, the mechanical properties of the prepared wear-resistant material decrease slightly. This may be because as the particle size of silicon carbide increases, it is not easy to be evenly dispersed in the reaction system, and the density between silicon carbide particles decreases, which will affect the mechanical properties and wear resistance of the wear-resistant material.
[0053] Combined with the test results of Example 2, Examples 9-11 and Table 5, it can be seen that when preparing the lithium magnesium silicate sol, the present application adds 1%-5% of diethylene glycol butyl ether acetate, wherein when the addition amount is 3%, a wear-resistant material with excellent wear resistance and mechanical properties can be prepared, while if diethylene glycol butyl ether acetate is not added, the viscosity of the lithium magnesium silicate sol is relatively large, and when mixed with other components, its dispersibility is relatively poor, thereby affecting the mechanical properties and wear resistance of the wear-resistant material. The interaction between diethylene glycol butyl ether acetate and the lithium magnesium silicate molecules is greater than the interaction between polyvinyl alcohol and lithium magnesium silicate, which helps to reduce the physical crosslinking points of lithium magnesium silicate between polyvinyl alcohol molecular chains, so adding diethylene glycol butyl ether acetate can reduce the gelation of the lithium magnesium silicate sol, thereby realizing the stable preparation of the lithium magnesium silicate sol; at the same time, the film-forming property of diethylene glycol butyl ether acetate is excellent, which helps to further improve the wear resistance of the wear-resistant material.
Claims
1. A wear-resistant material for sealing high-speed rotating parts, used in the friction working area between rotating parts and stationary parts, characterized in that: The wear-resistant material comprises the following components in parts by weight: 40-60 parts of silicon carbide, 10-30 parts of hydroxylated modified polyetheretherketone, 3-10 parts of composite fiber, 5-15 parts of magnesium silicate lithium sol, and 1-2 parts of silane coupling agent; The magnesium silicate lithium sol is prepared according to the following method: Mix polyvinyl alcohol and deionized water, and raise the temperature to 90-95°C while stirring until the polyvinyl alcohol is dissolved to form a polyvinyl alcohol aqueous solution with a mass concentration of 15%-20%; Then, lithium magnesium silicate is added into deionized water and magnetically stirred for 30-45 minutes to obtain a lithium magnesium silicate aqueous dispersion having a mass concentration of 0.8%-1.2%; Adding diethylene glycol butyl acetate to the lithium magnesium silicate aqueous dispersion, wherein the added mass of diethylene glycol butyl acetate is 1-5% of the lithium magnesium silicate dispersion, stirring evenly, then slowly dripping the polyvinyl alcohol aqueous solution, stirring at a temperature of 50-60° C. for 30-40 minutes, to obtain a mixed solution; The mixed solution is degassed in a vacuum degasser to obtain a magnesium silicate lithium sol.
2. The wear-resistant material for sealing a high-speed rotating part according to claim 1, characterized in that: The wear-resistant material comprises the following components in parts by weight: 45-55 parts of silicon carbide, 15-25 parts of hydroxylated modified polyetheretherketone, 5-8 parts of composite fiber, 8-12 parts of magnesium silicate lithium sol, and 1.2-1.8 parts of silane coupling agent.
3. The wear-resistant material for sealing a high-speed rotating part according to claim 1, characterized in that: The particle size of the silicon carbide is 30-50 μm.
4. The wear-resistant material for sealing a high-speed rotating part according to claim 1, characterized in that: The hydroxylation degree of the hydroxylated modified polyetheretherketone is 70%-85%.
5. The wear-resistant material for sealing a high-speed rotating part according to claim 1, characterized in that: The composite fiber is a mixture of carbon fiber and aramid fiber in a mass ratio of 1.8-2:
1.
6. The wear-resistant material for sealing a high-speed rotating part according to claim 5, characterized in that: The carbon fiber is a short-cut carbon fiber with a length of 1-3 mm, and the aramid fiber is a short-cut aramid fiber with a length of 100-200 μm.
7. A method for preparing a wear-resistant material for sealing a high-speed rotating part according to any one of claims 1 to 6, characterized in that: Prepared by the following steps: The composite fiber is placed in the magnesium silicate lithium sol and immersed at room temperature for 1-1.5 hours to obtain the magnesium silicate lithium sol immersed in the fiber; The hydroxylated modified polyetheretherketone is heated and melted, and the magnesium silicate lithium sol impregnated with the fiber and the silane coupling agent are added under stirring, and the mixture is mixed for 10-30 minutes; Add silicon carbide, mix and stir for 30-45 minutes, extrude and granulate to obtain wear-resistant material.
8. The method for preparing a wear-resistant material for sealing a high-speed rotating part according to claim 7, characterized in that: Place the composite fiber before the magnesium silicate lithium sol, evenly drip hydroxy silicone oil onto the surface of the composite fiber, and seal it for 12-24 hours.
9. The use of a wear-resistant material for sealing a high-speed rotating part according to any one of claims 1 to 7, characterized in that: The wear-resistant material can be used to process seals between high-speed rotating parts and stationary parts.
Citation Information
Patent Citations
Organic polymer and carborundum composite wear-resistant material and preparation method thereof
CN102504204B
Friction-reducing polymer material with dry-running capability and mechanical end-face seal with dry-running capability
CN105492516A
Wear-resistant polyether-ether-ketone composite material and preparation method thereof
CN108192276A
Multi-phase composite reinforced polyether ether ketone abrasion-resistant material
CN108250670A
Preparation method of silicon-carbon negative electrode material with high porosity and low volume expansion
CN118117081A